URSPRUNGSFOLK OCH RATTEN TILL SJÅLV-BESTÅMMANDE: Sjalvbestammandedoktrinen mot en ny mening? - Dahre, Ulf Johansson (Tidsskriftet Antropologi, 1996)
Ulf Johansson Dahre: Indigenous peoples and the right to self-determination: selfdetermination towards a new meaning? The beginning of the last decade of the 20th century has seen the end of a distinet era in international relations. This era, encompassing the years 1945-1990, was the era of decolonization, in which self-determination was defined or understood in relation to decolonization in the third world. This era also brought a distinet definition of self-determination. Entitled to self-determination were the peoples of European overseas colonies. Minorities and indigenous peoples excluded. However, a redefinition, or an extension of the concept, is ocurring. It is likely that self-determination will become a legal right of indigenous peoples, but not explicitly recognizing secession, but a right to political and social participation within the existing States. In the transition from colonial to postcolonial contexts, self-determination is becoming a means of conflict resolution and a way of pushing for democratic rights, also for indigenous peoples.